Morphological characterization of incisors and molars of an african descent group of Cali, Valle del Cauca (Colombia) - Garcia, Annie; Gustin, Fernando; Quiñonez, Catalina; Sacanamboy, Lina; Torres, Mery-Hann; Triana, Lina; Valencia, Diana; Rojas, Edwin; Gómez, Jaime; Moreno, Freddy (Revista Estomatología, 2015)
Objectives: To determine the frequency, variability, sexual dimorphism, correlation and bilateral symmetry of 13 non-metric dental crown traits (NMDCT) in incisors and molars of afro descent group of Cali, Valle del Cauca (Colombia) Material and methods: Quantitative cross-sectional study that characterizes the dental morphology of the central and lateral upper incisors (11, 12, 21, 22) and first and second upper and lower molars (16, 17, 26, 27, 36, 37, 46, 47) by ASUDAS system of observation, recording and analysis reported in the literature; from 60 models of study (34 female and 26 male) obtained from a afro descent group with aged between 7 to 17 years. Results: Was obtained winging and crowding mid frequencies, high frequency of shovel-shape in central and lateral incisors, low frequency of Carabelli cusp, low frequency of metaconule, reduction of hypocone absent, P point expression of protostylid, low frequency of deflecting wrinkle, groove pattern configuration Y5 (lower first molar) and +5 and +6 (lower second molar). NMDCT not sexually dimorphic (except hypocone reduction and groove pattern), have low correspondence and have bilateral symmetry. A p<0.05 was considered statistically significant. Conclusions: The frequency and variability of the 13 NMDCT allowed determining that the group of African descent is part of Caucasoid Dental Complex with Mongoloid Dental Complex influence, due to mixing processes and ethno historic settlement of the southeastern region of Cali. Key words: Dental anthropology, dental morphology, incisors, molars, non-metric dental traits, African descent, Afrocolombian.